Pengaruh Model Pembelajaran Projek Based Learning dan Motivasi Belajar terhadap Keterampilan Menulis Teks Anekdot Siswa Fase E SMAN 3 Painan - Maino, Restu; Morelent, Yetty; Syofiani, Syofiani (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2024)
This study is aimed to determine: (1) the difference of students’ writing anecdot text ability between low and high motivated students taught by Project Based Learning model and conventional learning; and (2) the effect of learning approach and learning motivation in writing news text ability. The theory that became the reference in this research is the contextual opinion of Johnson and Komalasari, theory of motivation is adopted from Sardiman, and writing news text is gotten from Panggabean. This study is a quasi experimental design with non-equivalent control group design. The population in this study was all students of class X SMAN 3 Painan, the total number of students is 120. The sampling technique is cluster sampling technique. The sample was X E1 as experiment class, and X E2 as control class. Based on data analysis, the result of research was done at the 95% level of confidence: (1) The improvement of writing news ability of students taught by using contextual learning was significantly higher than students taught using the conventional learning because t_observed = 7.48> t_table = 2,021; it can be seen that the students' response in the process of teaching and learning by using contextual learning is better (2) the improvement in the students' writing news ability who have low learning motivation which is taught using a contextual learning is significantly higher than the students who have low learning motivation taught by using the conventional learning, with t_observed = 6.99> t_table = 2.048; (3) the improvement of students' writing news ability with high learning motivation which is taught by using a contextual learning is considerably higher than students who have high learning motivation taught by using conventional learning, t_observed = 2,36> t_tabel = 2,048 (4) there is an interaction between learning approach and student's learning motivation on year twelve students' writing anecdot text ability at SMAN 3 Painan, with Fobserved = 5,554 <Ftable = 4,02; in conclusion, the contextual learning can be used as an appropriate learning approach and improve the learning outcomes of news text writing ability.